EFFUSIVE CONSTRICTIVE PERICARDITIS: HOW TO DIFFERENTIATE WITH CARDIAC TAMPONADE - Sukanto, Wega; Tangkilisan, Adrian; Tamburian, Christa; Stefanus, Gufi George (Riviera Publishing, 2023)
Constrictive-effusive pericarditis (ECP) is a rare syndrome but is gaining increasing attention in the classification of pericardial diseases. The aim of this research is to identify the differences in clinical symptoms between constrictive pericardial effusion and cardiac tamponade, such as chest pain, shortness of breath, blood pressure, heart rate, and other symptoms. We report the case of a 67-year-old man who had exertional dyspnea, lack of energy, fatigue, and pleuritic chest pain for the past 6 months. X-rays showed pericardial effusion and pericardial thickening with calcification indicating constrictive pericarditis. Echocardiographic examination also revealed similar findings. The patient then underwent pericardiectomy, during which the pericardial effusion was evacuated. However, after this procedure, cardiac contractions were still limited, underlying the constrictive process. This case illustrates the complexity in differentiating constrictive pericarditis from cardiac tamponade and the importance of accurate diagnosis in the management of this pericardial disease. In this case report, we discuss the clinical findings, diagnostic measures, and management implications in a patient with overt constrictive pericarditis.